Comments on “Axial vibration of double-walled carbon nanotubes using double-nanorod model with van der Waals force under Pasternak medium and magnetic effects [Vietnam Journal of Mechanics, Vol.44, No.1 (2022), pp. 29-43]” - Aydogdu, Metin (Vietnam Journal of Mechanics, 2022)
First of all Sentilkumar has to be congratulated for his paper [1]. In the paper, the author  presented the vibration of double walled carbon nanotubes. He claimed that the equations of motion given in [2]  are incorrect. The aim of this communication is to clarify this issue.